ИДЕОЛОГИЧЕСКИЙ КОНЦЕПТ «ПРЕЗИДЕНТ РОССИИ» В СОВРЕМЕННОМ РУССКОМ ПОЛИТИЧЕСКОМ ФЕЛЬЕТОНЕ - Sładkiewicz, Żanna (Przegląd Rusycystyczny, 2020)
In this article the author examines the notion of a conceptual picture of the world, the concept and ideology. Political feuilleton is part of the journalistic discourse qualifying as persuasive type of discourse. It always has an ideological mode and assumes public interest. The strategic feuilletonist’s task is to convince the reader the rightness of author’s world view. Understanding the information available to the individual is by its conceptualization. In this regard, the careful study of the basic concepts in a journalistic text is fundamentally important. This paper describes a content-conceptual filling of of the ideological construct “President of Russia” in the eight forms.